2016
DOI: 10.1038/srep32783
|View full text |Cite
|
Sign up to set email alerts
|

miR-762 promotes porcine immature Sertoli cell growth via the ring finger protein 4 (RNF4) gene

Abstract: A growing number of reports have revealed that microRNAs (miRNAs) play critical roles in spermatogenesis. Our previous study showed that miR-762 is differentially expressed in immature and mature testes of Large White boars. Our present data shows that miR-762 directly binds the 3′ untranslated region (3′UTR) of ring finger protein 4 (RNF4) and down-regulates RNF4 expression. A single nucleotide polymorphism (SNP) in the RNF4 3′UTR that is significantly associated with porcine sperm quality traits leads to a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 37 publications
0
52
0
1
Order By: Relevance
“…Considering the crucial role of immature SC in spermatogenesis, miRNAs act as important regulators in SC proliferation, maturation, and barrier regulation via the modulation of transcription factors involved in the cell cycle (Jiao et al, ; Ma et al, ; Yao et al, ). miR‐133b promoted SC proliferation by directly targeting the transcription factor GLI family zinc finger 3 and increased cyclin B1 and cyclin D11 expressions (Yao et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the crucial role of immature SC in spermatogenesis, miRNAs act as important regulators in SC proliferation, maturation, and barrier regulation via the modulation of transcription factors involved in the cell cycle (Jiao et al, ; Ma et al, ; Yao et al, ). miR‐133b promoted SC proliferation by directly targeting the transcription factor GLI family zinc finger 3 and increased cyclin B1 and cyclin D11 expressions (Yao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…miR‐133b promoted SC proliferation by directly targeting the transcription factor GLI family zinc finger 3 and increased cyclin B1 and cyclin D11 expressions (Yao et al, ). Ma et al () reported that miR‐762 mimic‐treated immature SCs promoted the proliferation through directly binding the 3ʹ‐UTR of ring finger protein 4, and Jiao et al () used a miR‐1285 mimic to promote SC proliferation through distinct pathways associated with the cell cycle. In addition, miR‐471 was found to be involved in SC metabolism and barrier function through downregulating desmocollin‐1 and forkhead box D1 (Panneerdoss et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence suggests that spermatogenesis is strictly regulated post‐transcriptionally, with small RNAs as the key regulators at this level (Mccubbin et al., ; Tang, Huang, Liu, & Zhang, ). For instance, miR‐20a might be a key inhibitor in the genistein‐induced slight abnormal spermatogenesis both in human and mice (Gu et al., ), and miR‐31 targets stimulated by retinoic acid gene 8 (Stra8) and inhibits spermatogenesis in spermatogonial stem cells (Wang et al., ), and miR‐17‐92 and miR‐762 in mice and pigs (Ma et al., ; Xie et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Swine testicular (ST) cells were purchased from BOSTER (ATCC ® CRL‐2528 ™ , Wuhan, China). ST cells were identified as porcine immature Sertoli cells and used in researches related to Sertoli cell function and maturation (Ma, Song, Guan, et al., ; Ma, Song, Yu, et al., ). Cells were cultured in high‐glucose Dulbecco’s modified Eagle’s medium (Hyclone, USA) with 10% foetal bovine serum (Gibco, Grand Island, NY, USA) at 37°C with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%